Vapor inhalation exposure to soman in conscious untreated rats: preliminary assessment of neurotoxicity. (2nd January 2016) - Perkins, Michael W.; Wong, Benjamin; Rodriguez, Ashley; Devorak, Jennifer L.; Dao, Thuy T.; Leuschner, Jessica A.; Kan, Robert K.; Sciuto, Alfred M.
Abstract: Neurological toxicity and brain injury following vapor inhalation exposure to the chemical warfare nerve agent (CWNA) soman (GD) were examined in untreated non-anesthetized rats. In this study, male Sprague-Dawley rats (300–350 g) were exposed to 600 mg × min/m 3 of soman or vehicle in a customized head-out inhalation system for 7 min. Convulsant animals were observed for clinical signs and various regions of the brain (dorsolateral thalamus, basolateral amygdala, piriform cortex, and lateral cortex) were collected for pathological observations 24 h post-exposure. Signs of CWNA-induced cholinergic crises including salivation, lacrimation, increased urination and defecation, and tremors were observed in all soman-exposed animals. Soman-exposed animals at 24 h post-exposure lost 11% of their body weight in comparison to 2% in vehicle-exposed animals. Whole blood acetylcholinesterase (AChE) activity was significantly inhibited in all soman-exposed groups in comparison to controls. Brain injury was confirmed by the neurological assessment of hematoxylin-eosin (H&E) staining and microscopy in the piriform cortex, dorsolateral thalamus, basolateral amygdala, and lateral cortex. Severe damage including prominent lesions, edematous, congested, and/or hemorrhagic tissues was observed in the piriform cortex, dorsolateral thalamus, and lateral cortex in soman-exposed animals 24 h post-exposure, while only minimal damage was observed in the basolateral amygdala. These results indicate that inhalation exposure to soman vapor causes neurological toxicity and brain injury in untreated unanesthetized rats. This study demonstrates the ability of the described soman vapor inhalation exposure model to cause neurological damage 24 h post-exposure in rats.